Developing a Gamified Metaverse for Practical Learning at Sukhothai Thammathirat Open University - Chaisaard, Nattasit; Sakulwichitsintu, Songlak (International Journal of Interactive Mobile Technologies (iJIM), 2026)
The purposes of this study was to develop a metaverse based on the gamification concept for the practical learning management of students at Sukhothai Thammathirat Open University (STOU) and to study their practical learning outcomes. The research findings showed that the metaverse, based on the gamification concept and developed for this model, consists of five components: (1) the context of the university or institute; (2) input, including learners, learning objectives, instructors, support personnel, the learning environment, and supporting technologies; (3) the process, involving teacher and learner preparation, implementation of learning activities, and measurement and evaluation of learning outcomes; (4) output, comprising academic achievement and learner satisfaction; and (5) the feedback for improving the design of the teaching and learning system. Additionally, students who studied with this metaverse achieved practical learning outcomes higher than the specified criteria, with a result of 69.7%. Furthermore, the evaluation of practical learning outcomes from the gamified metaverse was determined by assessing two behavioral components: Process Efficiency (E1) and Outcome Efficiency (E2); this served as a quality assurance tool, supporting teaching and learning achievements.